Basic directions and possibilities of sustainable development of tourism from the aspect of economic indicators of sustainability - Mountains case study - Turčinović, Milena; Vujko, Aleksandra; Knežević, Miroslav (Turizam, 2024)
The paper deals with the concept of sustainable tourism in mountainous, rural areas of Serbia and its economic indicators, i.e., the impact of economic indicators of sustainability on the local community, with the aim of pointing out the potential directions of tourism development. The research was conducted in selected rural areas of Zlatibor, Kopaonik, Stara Planina and Fruška Gora. Respondents expressed their opinion on the issue of sustainable tourism development, how sustainable tourism has contributed to the local community and the local population, which elements of sustainability have been fulfilled and in what way. It was concluded that residents of rural mountain destinations believe that truism directly and positively affects the sustainable development of rural destinations, thus confirming the initial hypothesis H that the economic indicators of sustainable tourism development provide a better quality of life for local communities.